Effectiveness of Bubble Breaths Relaxation to Reducing Anxiety in Early Childhood - Putrikita, Katrim Alifa; Widanarti, Mulianti (UPI Kampus Cibiru, 2024)
Children often struggle to express their emotions effectively. When experiencing anxiety, they may show behaviors such as startling easily, crying, or throwing tantrums. This study investigated the effectiveness of Bubble Breaths relaxation in reducing anxiety in early childhood. A quasi-experimental design with a one-group pretest-posttest design was employed. The participants were 18 Play Group students in Playgroup X, aged 3 to 5 years old. Saturated sampling was used to select the participants. Data analysis using a paired samples t-test revealed a significant difference between the pretest and posttest scores. The analysis showed a significant decrease in students' anxiety scores after the test compared to the pre-test scores, indicating that bubble breaths relaxation was effective in reducing anxiety levels in early childhood. In conclusion, bubble breath relaxation is effective for minimizing anxiety in early childhood. This is an effort to stimulate children so that their feelings of anxiety, sadness, and tantrums can be minimized. This research provides an impact for teachers and parents to identify children's feelings/emotions. from this, teachers can determine strategies to stimulate children to be able to express their emotions effectively, so that children feel comfortable with the approach the teacher takes.